Amelanotic Melanoma - A case report with review of literature - R Kamala; R Gopakumar; Subhas Babu; S Giridhar Naidu; Vidya AjiIa; Karthik Hegde (Wolters Kluwer Medknow Publications, 2007)
Oral malignant melanoma is a rare disease. Amelanotic melanoma is a subtype of cutaneous melanoma with little or no pigmentation. True AMM are rare and there may be some pigmentation at the periphery of the lesion. Amelanotic melanomas represent about 2-8 % of all malignant melanomas. The Clinical Diagnosis of Amelanotic melanomas can be difficult as these lesions may mimic different benign and malignant melanotic and nonmelanotic lesions because of their lack of pigmentation. Amelanotic melanomas often are diagnosed in advanced stage and have poor prognosis. The dental clinician must therefore carefully examine the head, neck, and oral cavity, and any pigmented lesion that exhibits growth potential must be biopsied. Early detection of melanoma is an indication for radical treatment and may increase the survival rate of patients with this disease.